MANAJEMEN PENDIDIKAN MANAJEMEN PENDIDIKAN MASA DEPAN BERBASIS KEDAMAIAN DI SMP NEGERI 2 SENTANI - Butu, Dorce (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
This study analyzes the implementation of peace education at Junior High School 2 Sentani and its impact on peace-based education management. Through a qualitative approach, data were collected through surveys, interviews and analysis of school documents. The results show that this school successfully integrates peace values in the lesson plans of several subjects and utilizes the Merdeka Curriculum to support the dimension of peace values. Teachers actively teach peace values through strategies such as the “Bestie Day” program and successfully overcome conflicts between schools and teach peace values. Measuring the integration of peace values in lesson plans and monitoring student character are used to measure peace-based education management. Peace education creates a harmonious school environment and peace-loving student characters, with positive impacts on society. The importance of a positive school climate and the role of teachers in shaping students' peaceful character. Teaching mutual understanding also helps create a harmonious environment and students' social skills. Thus, investing in peace education is a progressive step towards shaping students' character, creating a peaceful school environment and making a positive contribution to society. The implementation of peace education at the Junior High School 2 Sentani is an important step in the development of peace-based education management.